The design and manufacture of biomedical surfaces - Ramsden, Jeremy J.; Allen, David M.; Stephenson, David J.; Alcock, Jeffrey R.; Peggs, G. N.; Fuller, G. D.; Goch, G. (Technische Rundschau, Hallwag Publishers; 1999, 2007)
Surfaces are the primary place of contact between a biomaterial and its host organism. Typically, prostheses have to fulfil demanding structural and mechanical requirements, yet the material best for those functions may be bio- incompatible. Surface treatment or coating provides a means to overcome that problem, which means both integration within the host physiology and stabilization with respect to corrosion and wear. The adsorption of biomacromolecules is pivotal for biocompatibility. The impossibility of keeping proteins away from most implants means that very careful consideration has to be given to this aspect, and both prevention (for bloodstream implants) and promotion (for bone replacement and repair) occur with equal importance. This paper also considers the metrology of relevant physical and chemical aspects of surfaces.